Recovery of strength in locally versus globally thermally cracked freshwater ice produced in the laboratory and sea ice collected in the Beaufort Sea, 2022-2024 ... - Murdza, Andrii; Schulson, Erland; Renshaw, Carl (NSF Arctic Data Center, 2024)
The vulnerability of ocean and lake ice covers to climate change-induced threats, such as decreased extent and increased thermal cracking, necessitates comprehensive investigation. Conducted at Dartmouth College's Ice Research Laboratory from 2022 to 2024, experiments introduced thermal shock to laboratory-grown freshwater ice and natural first-year sea ice using liquid nitrogen to either a narrow band or the entire surface of ice samples. This study explores the impact of thermal cracking on the flexural strength. Results indicate that while both types of ice initially experience strength reduction after thermal shock, full recovery occurs when a narrow region is shocked, whereas only partial recovery is observed when the entire surface is shocked in freshwater ice, contrasting with full recovery in sea ice. Repeated cycles of cracking and healing do not affect flexural strength recovery. Moreover, experiments involving creep reveal the influence of compressive stress on healing, highlighting its role in ...